2020
DOI: 10.3389/fnmol.2019.00319
|View full text |Cite
|
Sign up to set email alerts
|

Oligomers Are Promising Targets for Drug Development in the Treatment of Proteinopathies

Abstract: Currently, there is no effective treatment of proteinopathies, as well as their diagnosis in the early stages of the disease until the first clinical symptoms appear. The proposed model of fibrillation of the Aβ peptide and its fragments not only describes molecular rearrangements, but also offers models of processes that occur during the formation of amyloid aggregates. Since this model is also characteristic of other proteins and peptides, a new potential target for drug development in the treatment of Alzhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 69 publications
0
29
0
Order By: Relevance
“…The full-length S1 protein has a high mobility of individual protein domains and a tendency to aggregation, which creates problems for establishing its three-dimensional structure [ 203 , 204 ]. At the same time, using computational and experimental approaches, we described specific amyloidogenic regions within the domains of the S1 protein, which can be potential sites for modulating the aggregation properties of bacterial ribosomal S1 proteins [ 9 , 205 , 206 , 207 ]. Based on the predicted amyloidogenic regions, amyloidogenic peptides were synthesized, some of which exhibited antimicrobial activity in vitro tests [ 16 ].…”
Section: Mechanisms Of Antimicrobial Action Of Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…The full-length S1 protein has a high mobility of individual protein domains and a tendency to aggregation, which creates problems for establishing its three-dimensional structure [ 203 , 204 ]. At the same time, using computational and experimental approaches, we described specific amyloidogenic regions within the domains of the S1 protein, which can be potential sites for modulating the aggregation properties of bacterial ribosomal S1 proteins [ 9 , 205 , 206 , 207 ]. Based on the predicted amyloidogenic regions, amyloidogenic peptides were synthesized, some of which exhibited antimicrobial activity in vitro tests [ 16 ].…”
Section: Mechanisms Of Antimicrobial Action Of Peptidesmentioning
confidence: 99%
“…Of particular interest is the potential for the use of peptides, which, in addition to pronounced antimicrobial properties, also tend to self-assembly, the formation of supramolecular complexes, and amyloidogenesis [ 5 , 6 , 7 ]. Traditionally, the amyloidogenic properties of peptides are negatively regarded as contributing to the development of neurodegenerative and progressive metabolic diseases [ 8 , 9 , 10 ]. However, in recent years, more and more attention has been paid to the study of the functional role of amyloidogenic peptides in the protection of the host and the prospects for their use as antimicrobial agents [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the propensity of some proteins and peptides to form oligomers without fibril formation, as expected, can be used to predict their amyloidogenicity, as was suggested [ 22 ]. Previously, it was shown that the formation of oligomers is a key event that determines the pathway of fibrillation [ 23 , 44 , 45 ], as well as a polymorphism of fibrils [ 46 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The misfolding and extracellular aggregation of Aβ peptides have been recognized as the main cause of AD progression, leading to the formation of toxic Aβ oligomers and deposition of β-amyloid plaques in the brain [61]. It has been suggested that oligomeric Aβ species may represent a valid biological target [66,155,156].…”
Section: Misfolded Aβ In Admentioning
confidence: 99%